2023
DOI: 10.1097/md.0000000000033101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duloxetine on pain relief after total knee arthroplasty: A meta-analysis of randomized controlled trials

Abstract: Background: Postoperative pain is one of the most feared complications of total knee arthroplasty. Recently, randomized controlled trials have compared the efficacy of duloxetine in patients undergoing total knee arthroplasty. However, there is no definite answer as to the efficacy and safety of duloxetine. Methods: Randomized controlled trials about relevant studies were searched from PubMed (1996 to July 2022), Embase (1996 to July 2022), and Cochrane Library (CENTRAL, July 2022). Results: Six high-quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Data on the analgesic effectiveness of duloxetine differ among the studies discussed: Yang et al reported a significant reduction in pain in the range from three days to eight weeks after the procedure, while Zhou et al noted the above effect only within the first 24h after surgery. In all the mentioned works, the authors pointed to the small amount of material available for analysis, and therefore reported the need to conduct further, large, well-designed RCTs [32][33][34]. In another metaanalysis assessing the effectiveness of duloxetine for postoperative pain control after total knee or hip arthroplasty, Jones et al reported a reduction in opoid consumption 48 and 72h after surgery in patients taking the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the analgesic effectiveness of duloxetine differ among the studies discussed: Yang et al reported a significant reduction in pain in the range from three days to eight weeks after the procedure, while Zhou et al noted the above effect only within the first 24h after surgery. In all the mentioned works, the authors pointed to the small amount of material available for analysis, and therefore reported the need to conduct further, large, well-designed RCTs [32][33][34]. In another metaanalysis assessing the effectiveness of duloxetine for postoperative pain control after total knee or hip arthroplasty, Jones et al reported a reduction in opoid consumption 48 and 72h after surgery in patients taking the drug.…”
Section: Discussionmentioning
confidence: 99%